2003
DOI: 10.1128/jvi.77.24.13439-13447.2003
|View full text |Cite
|
Sign up to set email alerts
|

DeNovo Infection with Rhesus Monkey Rhadinovirus Leads to theAccumulation of Multiple Intranuclear Capsid Species during LyticReplication but Favors the Release of Genome-ContainingVirions

Abstract: Rhesus monkey rhadinovirus (RRV) is one of the closest phylogenetic relatives to the human pathogenKaposi's sarcoma-associated herpesvirus (KSHV), yet it has the distinct experimental advantage of entering efficiently into lytic replication and growing to high titers in culture. RRV therefore holds promise as a potentially attractive model with which to study gammaherpesvirus structure and assembly. We have isolated RRV capsids, determined their molecular composition, and identified the genes encoding five of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 56 publications
(61 reference statements)
1
19
0
Order By: Relevance
“…However, this could seem unlikely given the tight packing of DNA which requires the entire internal content of the capsid (5). B capsids could also be released from dying cells or particles that lack DNA could occasionally bud, as previously observed for KSHV and RRV (39,40). This would explain the detection of the BoHV-4 pORF17.5 in our samples (see Fig.…”
Section: Discussionsupporting
confidence: 63%
“…However, this could seem unlikely given the tight packing of DNA which requires the entire internal content of the capsid (5). B capsids could also be released from dying cells or particles that lack DNA could occasionally bud, as previously observed for KSHV and RRV (39,40). This would explain the detection of the BoHV-4 pORF17.5 in our samples (see Fig.…”
Section: Discussionsupporting
confidence: 63%
“…In contrast, rhesus monkey rhadinovirus (RRV), a nonhuman primate gamma-2 herpesvirus with high levels of homology to KSHV, grows to high titer in culture (2,33,47,64). We have previously characterized the capsids of both KSHV and RRV (30,33,56,64). In these studies, we found that the three-dimensional capsid structures and protein homolog compositions were strikingly similar (33, 64).…”
mentioning
confidence: 95%
“…Unfortunately, KSHV grows to low titer in culture, making detailed structural and compositional studies of highly purified particles particularly challenging (4,65). In contrast, rhesus monkey rhadinovirus (RRV), a nonhuman primate gamma-2 herpesvirus with high levels of homology to KSHV, grows to high titer in culture (2,33,47,64). We have previously characterized the capsids of both KSHV and RRV (30,33,56,64).…”
mentioning
confidence: 99%
“…First, the RRV life cycle can be modeled in vivo, in rhesus macaques. Second, RhF support 100% lytic replication of RRV and allows for the production of high titers of virus (ϳ10 6 PFU/ml) (58). Our group has demonstrated that the transcription program of RRV is similar to that of KSHV (17,25).…”
mentioning
confidence: 97%